Reinventing rural economies through sustainable business models: a triple-layered analysis - Dionizi, Brikene; Dhora, Romina (Frontiers in Sustainability, 2025)
Albania’s transition from a centralized to a market economy has resulted in a fragmented and mostly informal business landscape, where small enterprises dominate and sustainability-oriented strategies remain underdeveloped. However, with EU accession, Agenda 2030 commitments, and global climate objectives, there is a growing urgency to align local business models with circular and inclusive practices. This study aimed to explore how sustainable business model frameworks can be effectively applied in emerging contexts by the Triple Layered Business Model Canvas (TLBMC) to Mrizi Zanave, a leading agrotourism enterprise in North Albania. The research employs a qualitative case study approach, combining two semi-structured interviews with founders/managers and desk research across multiple data sources, including the National Business Center registry, company websites, and social media communications. The results indicated that Mrizi Zanave creates value across economic, social, and environmental layers by embedding traditional knowledge, regional supply chains, and community-based employment. Quantitatively, the enterprise cooperates with 400 smallholder farmers, employs 105 staff and hosts approximately 90,000 visitors annually [As by the latest data delivered by the company on National Business Center registry (data for the business fiscal year 2024)]. However, formal measurement of environmental and social impacts remains limited, reflecting institutional and infrastructural constraints. By operationalizing the TLBMC in a context shaped by structural informality and historical marginalization, the study contributes to the international literature on business model innovation in post-socialist and emerging European contexts, particularly within the Western Balkans. It highlights both the opportunities and challenges of place-based entrepreneurship for sustainable rural generation in the Western Balkans.